Radzenie sobie ze stresem rodziców dzieci z autyzmem - Dudek, Mieczysław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The appearance of a child with a disability is always a source of tremendous stress in the family. This problem is particularly evident in the case of an autistic child because of its unpredictable and untypical development. Every person during their life develops certain mechanisms to deal with difficult situations. According to Lazarus and Folkman (1987), dealing with stress mainly relies on specific intellectual activities and appropriate actions to control the requirements assessed by the person as burdensome or beyond his/her current possibilities. There are many ways of dealing with stress. The most common strategies include those focused on solving the problem (SSZ), emotional overreaction (SSE) and avoidance of stress (SSU) by engaging in substitute activities (ACZ) or seeking social interaction (CSA). It is assumed that an effective way to deal with stress consists in relating the needs and capabilities of an individual. The aim of this article was to investigate the ways of dealing with stress among 130 parents of autistic children.